2010
DOI: 10.1093/cvr/cvq129
|View full text |Cite
|
Sign up to set email alerts
|

Postconditioning and protection from reperfusion injury: where do we stand? * Position Paper from the Working Group of Cellular Biology of the Heart of the European Society of Cardiology

Abstract: Ischaemic postconditioning (brief periods of ischaemia alternating with brief periods of reflow applied at the onset of reperfusion following sustained ischaemia) effectively reduces myocardial infarct size in all species tested so far, including humans. Ischaemic postconditioning is a simple and safe manoeuvre, but because reperfusion injury is initiated within minutes of reflow, postconditioning must be applied at the onset of reperfusion. The mechanisms of protection by postconditioning include: formation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
311
1
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 453 publications
(329 citation statements)
references
References 202 publications
12
311
1
5
Order By: Relevance
“…The RISK and SAFE pathways are known as major protective signaling cascades in both ischemic pre‐ and postconditioning 21. Phosphorylation of ERK1/2, AKT, and STAT3 represents RISK and SAFE activation 22.…”
Section: Resultsmentioning
confidence: 99%
“…The RISK and SAFE pathways are known as major protective signaling cascades in both ischemic pre‐ and postconditioning 21. Phosphorylation of ERK1/2, AKT, and STAT3 represents RISK and SAFE activation 22.…”
Section: Resultsmentioning
confidence: 99%
“…The beneficial effect of RVP on infarct size was further confirmed by a reduction in LDH release into the coronary effluent. Infarct size is a key determinant of major clinical outcomes (mortality and morbidity of consequent heart failure) (Gibbons et al, 2004); therefore, development of procedures that effectively decrease infarct size along with reperfusion therapy is in the focus of preclinical and clinical studies (Ovize et al, 2010). IPost is a widely studied approach, and the infarct size-reducing effect of this procedure was confirmed in various mice, rat, rabbit, dog and swine animal models (Skyschally et al, 2009b) as well as in clinical trials (Ovize et al, 2010).…”
Section: Figurementioning
confidence: 99%
“…Infarct size is a key determinant of major clinical outcomes (mortality and morbidity of consequent heart failure) (Gibbons et al, 2004); therefore, development of procedures that effectively decrease infarct size along with reperfusion therapy is in the focus of preclinical and clinical studies (Ovize et al, 2010). IPost is a widely studied approach, and the infarct size-reducing effect of this procedure was confirmed in various mice, rat, rabbit, dog and swine animal models (Skyschally et al, 2009b) as well as in clinical trials (Ovize et al, 2010). However, some studies reported the ineffectiveness of IPost in animal models (Dow and Kloner, 2007;Skyschally et al, 2009b) and in clinical trials (Hahn et al, 2013).…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations